2005
DOI: 10.1200/jco.2005.07.740
|View full text |Cite
|
Sign up to set email alerts
|

Oxaliplatin, Fluorouracil, and Leucovorin for Patients With Unresectable Liver-Only Metastases From Colorectal Cancer: A North Central Cancer Treatment Group Phase II Study

Abstract: Our data suggest that FOLFOX4 has a high response rate (complete response, partial response, or reduction) in patients with liver-only metastases from colorectal cancer, allowing for successful resection of disease in a portion of patients initially not judged to be optimally resectable. However, a high recurrence rate after surgery was observed, which, in 73% of patients, involved the liver. Further trials are indicated based on the promising results observed in this trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
228
1
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(248 citation statements)
references
References 17 publications
6
228
1
7
Order By: Relevance
“…The recent phase II study of Alberts et al (2005) confirmed the efficacy of FOLFOX4 in the neoadjuvant setting, with 25 of the 42 (60%) assessable patients with nonoptimally resectable liver-only metastatic disease showing a reduction of tumour burden and 17 (40%) patients subsequently undergoing surgery following a median of 6 months of chemotherapy. A high recurrence rate of 71% after a median follow-up of 22 months was observed in this study for patients who underwent complete resection.…”
Section: Hepatic Resectionmentioning
confidence: 89%
“…The recent phase II study of Alberts et al (2005) confirmed the efficacy of FOLFOX4 in the neoadjuvant setting, with 25 of the 42 (60%) assessable patients with nonoptimally resectable liver-only metastatic disease showing a reduction of tumour burden and 17 (40%) patients subsequently undergoing surgery following a median of 6 months of chemotherapy. A high recurrence rate of 71% after a median follow-up of 22 months was observed in this study for patients who underwent complete resection.…”
Section: Hepatic Resectionmentioning
confidence: 89%
“…Similarly, two-stage hepatectomies in CRLM involve delayed re-hepatectomy after hypertrophy of the residual liver and may be used for large bilateral lesions in which a one stage resection of all the involved segments would lead to liver failure (19). Modern chemotherapeutic regimens combining 5-FU, folinic acid and oxaliplatin and/or irinotecan are associated with much higher response rates and can allow 10-30% of patients with initially unresectable CRLM to be successfully treated with liver surgery (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…5-Fluorouracil (5-FU), leucovorin and oxaliplatin (Oxa) represent a therapeutic regime (FOLFOX) commonly used in the treatment of patients with advanced colon cancer. [4][5][6] Resistance to therapy occurs in nearly all patients with metastatic colon cancer, and patients that acquire resistance have a disease progression with few therapeutic options. As the gain of drug resistance involves the acquisition of a new phenotype, we hypothesized that the generation of fused cells in metastatic colon cancer could represent a phenomenon responsible of MDR.…”
Section: Introductionmentioning
confidence: 99%